Korelasi Antara Gaya Koping dan Perilaku Asertif Pada Siswa - Sugara, Gian Sugiana; Rahmawati, Eka; Muhajirin, Muhammad (JKI (Jurnal Konseling Indonesia), 2023)
The aim of this research is to determine the correlation between coping styles and assertive behavior in students and the comparison based on gender and to plan coping skills training to increase assertive behavior in students. This research uses a quantitative descriptive approach with a correlational design to reveal the correlation regarding coping styles and assertive behavior in students. The measuring instruments used are an inventory of assertive behavior and an inventory of coping styles. Participants in this research were 220 students. Sampling uses random sampling techniques, that is, all members of the population have the same opportunity to be sampled. The data analysis technique uses the Pearson correlation method to determine the relationship between coping styles and assertive behavior in students. The F-Test technique is used to compare differences in coping styles based on gender. The research results show that men's assertive behavior is higher than women's. There is no difference in adaptive and maladaptive coping styles between men and women.